Moving Forward on Gang Prevention in Los Angeles, California, 2009-2014 - Hennigan, Karen ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed.Using multiple data time points this study investigated the prospective validity of a secondary gang prevention program called Gang Risk of Entry Factors (GREF) assessment. At Time 1 of the study interview cut-points were established for high and low risk on nine risk factors that were included on the assessment. Those who scored high risk on four or more risk factors were determined eligible for secondary prevention. At time 2 each participate was then classified into one of four levels of gang membership. The goal of this was to investigate how successful the GREF was in identifying the youth (in the absence of a program) who become associated with a street gang in the 12 to 18 months of the study time frame .